Distance-dependent electron transfer rate of immobilized redox proteins: A statistical physics approach - Georg, Sören (2010)
The electron transfer kinetics of redox proteins adsorbed on metal electrodes coated with self-assembled monolayers (SAMs) of mercaptanes shows an unusual distance-dependence. For thick SAMs, the experimentally measured electron transfer rate constant kexp obeys the behavior predicted by Marcus theory, whereas for thin SAMs, kexp remains virtually constant. In this work, we present a simple theoretical model system for the redox protein cytochrome c electrostatically bound to a SAM-coated electrode. A statistical average of the electron tunneling rate is calculated by accounting for all possible orientations of the model protein. This approach, which takes into account the electric field dependent orientational distribution, allows for a satisfactory description of the "saturation" regime in the high electric field limit. It further predicts a nonexponential behavior of the average electron transfer processes that may be experimentally checked by extending kinetic experiments to shorter sampling times, i.e., 1/ kexp. For a comprehensive description of the overall kinetics in the saturation regime at sampling times of the order of 1/ kexp, it is essential to consider the dynamics of protein reorientation, which is not implemented in the present model. © 2010 The American Physical Society.